2023
DOI: 10.1002/oby.23695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a population‐scaled, school‐based physical activity intervention for the prevention of childhood obesity

Abstract: ObjectiveThe aim of this study was to examine the effectiveness of a real‐world, population‐scaled, school‐based physical activity (PA) intervention that provided two to three additional physical education lessons per week to children aged 6 to 14 years in Slovenia.MethodsMore than 34,000 participants from over 200 schools were compared with a similar number of nonparticipants from the same schools. Generalized estimating equations were used to estimate the effects of differing levels of exposure to the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The impact of COVID-19 measures on children’s physical activity was global, but Slovenia might have been more affected by the COVID-19 measures (especially school closures) than most other countries as they do not have so many physical activity initiatives implemented through the school system. Our recent analysis of a scaled-up physical activity intervention showed that the Slovenian advantage in terms of maintaining and improving the physical fitness of children lies in the educational setting, 49 and demonstrates that Slovenia has the knowledge and experience needed to combat the current situation. Results of this study were already presented in front of the Slovenian parliament which decided to prepare the grounds for the re-launch of a nationwide physical activity programme in schools (i.e., Healthy Lifestyle Intervention ), which still did not happen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COVID-19 measures on children’s physical activity was global, but Slovenia might have been more affected by the COVID-19 measures (especially school closures) than most other countries as they do not have so many physical activity initiatives implemented through the school system. Our recent analysis of a scaled-up physical activity intervention showed that the Slovenian advantage in terms of maintaining and improving the physical fitness of children lies in the educational setting, 49 and demonstrates that Slovenia has the knowledge and experience needed to combat the current situation. Results of this study were already presented in front of the Slovenian parliament which decided to prepare the grounds for the re-launch of a nationwide physical activity programme in schools (i.e., Healthy Lifestyle Intervention ), which still did not happen.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting physical activity and healthy habits in children can be challenging, but there are a variety of strategies that can be used to encourage children to engage in physical activity and maintain healthy lifestyles. These include promoting active transportation, such as walking or biking to school, 50 providing opportunities for structured physical activity during the school day, 49 , 51 and providing access to safe and affordable recreational facilities. 52 Additionally, educating parents and caregivers about the importance of physical activity and healthy lifestyles can help to promote healthy habits in children from an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Slovenia was successful in achieving economic recovery and has become an integrated part of the Western European market. 64 After the transition period that Slovenia was experiencing the trends were in part reversed in the 2010s with an effective school-based national physical activity programme "Healthy Lifestyle", 65 and an aggressive media campaign about proper diet and media consumption. Therefore, as Slovenia has been facing negative lifestyle changes in recent decades, it seems that implementing several nationwide initiatives and curriculum updates, especially within the educational system, could have led to the improvements in fitness witnessed during the 2010s in this study and earlier studies from Slovenia.…”
Section: Discussionmentioning
confidence: 99%
“…By launching a free-for-use, multi-lingual, online child fitness portal based on updated reference values, 35 there is concerted efforts being made to close the gap in terms of child fitness standardisation, accessibility and monitoring worldwide (available online here: fitbackeurope.eu/en-us/). Establishing long-duration, population-scaled PA intervention studies can reverse negative health trends (like obesity), 36 but this must come with a willingness to invest in future health outcomes now. Maintaining childhood fitness will become increasingly important in an ever-changing world, especially as global warming, 32 conflict, and rapid changes in technology continue to push societies in continuous and unexpected ways.…”
Section: Discussionmentioning
confidence: 99%